Medical, psychological and psychopathological indicators of psychological distress in family members of a cancer patient at different stages of treatment - Abdriahkimova, Ts. B.; Murakhovskaya, I. R.; Kleban, K. I.; Sapon, D. M. (Journal of Education, Health and Sport, 2017)
The study of the peculiarities of psychological state of a cancer patient’s relatives in connection with the main disease treatment has shown that the components of the psychological burden on family members are their own mental distress on connection with the illness of a dear person, increasing family responsibilities, psycho-emotional support on the patient, participation on the organization treatment measures. The spectrum of psychological problems of family members includes 4 content blocks: lack on information, on experiences, interaction with the patient, involvement in treatment. It was diagnosed that mental changes on relatives on cancer patients manifested anxiety-depressive mood, internal tension, somatization on anxiety, obsessive thoughts about illness, doubts about the correctness on their actions, sensitivity to patient’s statements, outbreaks on anger.